TESTING TECHNIQUE OF MOTOR PETROL PHYSICAL STABILITY ESTIMATION AND FORECASTING - Boychenko, Sergey V.; Sidorenko, Nina A.; Chernyak, Larisa N.; Pugachevskaya, Eugenya P. (Proceedings of National Aviation University (archive), 2009)
The technique of petrol physical stability assessment and forecasting was tested. The results of study aimed at investigation of modern motor petrols evaporability are presented in the article. The refractive index is shown to be useful tool in making prognosis about evaporation losses of motor petrol. The validation of this technique was conducted and recommendations are given on its application.